Hubungan Gaya Kepemimpinan Transaksional dengan Kepuasan Kerja Karyawan PT. Socfindo Aek Pamingke Divisi V - Afwina, Rahma; Al Fiqri, Muhammad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The aim of this study is to investigated the correlational between transactional leadership style and job satisfaction of employees PT. Socfindo Aek Pamingke Division V. The approach used to this study is quantitative research. The study participants were 81 of employees at Division V. They were selected making use of purposive sampling that is the sample were taken based on their characteristics, namely employees of PT. Socfindo Aek Pamingke Division V, under 50 years, work range 5 years and above. The hypothesis in this study was a positive correlational between transactional leadership style and job satisfaction of PT. Socfindo Aek Pamingke Division V employeesâ€. Assuming that the more effective the transactional leadership style is, the higher the employee's job satisfaction. Conversely, the less effective the transactional leadership style, the lower employee job satisfaction. Data collection uses a Likert scale, where alternative answers consist of four categories. The assessment given to each subject's answer to each favorable statement is Strongly Agree (SS) with a value of 4, Agree (S) with a value of 3, Disagree (TS) with a value of 2, Strongly Disagree (STS) with a value of 1. The unfavorable statements are Strongly Agree (SS) with a value of 1, Agree (S) with a value of 2, Disagree with a value of 3, strongly disagree (STS) with a value of 4. Based on data analysis, the coefficient rxy = 0.673. With a significance value of P < 0.000. Shows that the transactional leadership style contributes to job satisfaction of 45.3%. So, there is a positive relationship between transactional leadership style and employee job satisfaction. From the results obtained, it can be stated that the proposed hypothesis is accepted.